The Influence of Celebrity Endorsement and Electronic Word of Mouth on Purchase Decisions on Shopee With Consumer Confidence as a Moderation Variable in Islamic Business Perspective (Study on Shopee Generation Z Consumers in Bandar Lampung) - Rina Jesica; Zulaikah Zulaikah; Yeni Susanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study was to determine and analyze the celebrity endorsement and electronic word of mouth towards purchase decisions on shopee with consumer confidence as a moderation variable in the perspective of Islamic Business. This study uses a quantitative approach. The population in this study was 2,228 Generation Z in Bandar Lampung. The sampling technique used is non probability sampling, using the slovin formula, and getting a sample number of Shopee consumers as many as 96 respondents. Data analysis techniques used in the study using Moderated Analysis (MRA) with SmarPLS 4. Based on the results of statistical analysis, Celebrity Endorsement has a positive and significant effect on purchase decisions on Shopee, and Electronic Word of Mouth does not have a positive and significant effect on purchase decisions on Shopee. Consumer confidence strengthens the influence of Celebrity Endorsement on purchase decisions on Shopee, but consumer confidence weakens the influence of Electronic Word of Mouth on purchase decisions on Shopee. In an Islamic perspective, digital business practices such as Shopee must be run with the principles of honesty, justice, and responsibility as a form of worship, where consumer trust is built through transparency, ethical communication, and promotion that is not excessive in accordance with Sharia values.